Demographic Variables and Psychological Well-being of Teachers - Saraf, Papia; Murthy, C.G. Venkatesh (INDIAN EDUCATIONAL REVIEW, 2020)
A teacher’s psychological well-being impacts not only their teaching effectiveness but has far reaching effects on both the psychological well-being and achievement of the students. Even though teaching is now recognised as a stressful job causing burnout, understanding and promoting teacher psychological well-being remains a neglected area. Recognising that psychological well-being is a human characteristic not necessarily induced by the work context, this paper intended to understand the demographic variables that may have an impact on the psychological well-being of a teacher. These demographic variables included gender, marital status, years of work experience and college affiliations. To this end the psychological well-being of undergraduate degree college and higher secondary teachers were assessed using the psychological well-being PWB 20 scale (Mehrotra, Tripathi, and Ban, 2013). The sample consisted of 945 teachers (622 professional degree college teachers, 198 academic degree college teachers and 125 higher secondary teachers). The results indicated that the professional degree college teachers had significantly better psychological well-being levels than both academic degree college and higher secondary teachers. Demographic variables, such as gender and marital status did not impacted psychological well-being. However, years of experience did have a differential impact on psychological well-being. The implications of the study are discussed in the paper.